A drop of corruption : an Ana and Din mystery - Bennett, Robert Jackson, 1984- (Bennett, Robert Jackson, 1984- Shadow of the Leviathan ;, 2025)
Ana and Din are sent to the opposite fringe of the Empire to solve what appears to be a classic locked-room murder mystery. But no case that Special Investigations sends their most special team to is ever that simple. The moment that eccentric senior investigator Ana is on the scene, she knows that the case is about something no one wants to admit..."